Dialogical Family Guidance (dfg)-Development and implementation of an intervention for families with a child with neurodevelopmental disorders - Diana Cavonius‐Rintahaka; Anna Liisa Aho; Eva Billstedt; Christopher Gillberg (Wiley, 2021)
Abstract Aim To describe the development and implementation of a Dialogical Family Guidance (DFG) intervention, aimed at families with a child with neurodevelopmental disorders (NDD). Design The DFG components are presented and the content of a DFG training course. Professionals' experiences after the DFG training were evaluated. Methods Dialogical Family Guidance development phases and implementation process are examined. The Revised Standards for Quality Improvement Reporting Excellence checklist (SQUIRE 2.0) was used to provide a framework for reporting new knowledge. Results The DFG training course seemed to increase possibilities of a more independent role as a nurse to deliver the DFG family intervention. The project showed that the use of dialogue can be difficult for some professionals. Analysis of the questionnaire completed after DFG training reported a high level of satisfaction. DFG training offered a new approach to deliver knowledge and understanding to families using dialogue, including tailored psychoeducation and emotional and practical guidance.